Bronchiectasis Is a Model for Chronic Bacterial Infection Inducing Autoimmunity in Rheumatoid Arthritis. Issue 9 (September 2015) - Quirke, Anne‐Marie; Perry, Elizabeth; Cartwright, Alison; Kelly, Clive; De Soyza, Anthony; Eggleton, Paul; Hutchinson, David; Venables, Patrick J.
<x xml:space="preserve">Abstract</x> Objective To examine the potential of chronic severe bacterial infection to generate rheumatoid factor (RF) and anti–citrullinated protein antibodies (ACPAs), by studying patients with bronchiectasis (BR) alone and BR patients with rheumatoid arthritis (BR/RA). Methods We studied 122 patients with BR alone, 50 patients with BR/RA, and 50 RA patients without lung disease, as well as 87 patients with asthma and 79 healthy subjects as controls. RF levels were measured using an automated analyzer, and cyclic citrullinated peptide 2 (CCP‐2) was used to detect ACPAs. The fine specificities of citrullinated α‐enolase peptide 1 (CEP‐1), Cit‐vimentin, and Cit‐fibrinogen to their arginine‐containing control peptides (arginine‐containing α‐enolase peptide 1 [REP‐1], vimentin, and fibrinogen) were measured by enzyme‐linked immunosorbent assay. Results Among the BR patients and control subjects, 39% and 42%, respectively, were ever‐smokers. The frequency of RF positivity in serum was increased in BR patients compared with controls (25% versus 10%), as were the frequencies of antibodies to CCP‐2 (5% versus 0%), CEP‐1 (7% versus 4%), Cit‐vimentin (7% versus 4%), and Cit‐fibrinogen (12% versus 4%), although only the differences for RF and Cit‐fibrinogen were significant (P < 0.05). We observed a corresponding increase in the frequency of antibodies to the arginine‐containing control peptides in BR patients compared with controls (for REP‐1, 19% versus 4% [P < 0.01]; for vimentin, 16% versus 4% [P < 0.05]), demonstrating that the ACPA response in patients with BR is not citrulline specific. The lack of citrulline specificity was further confirmed by absorption studies. In BR/RA patients, all ACPA responses were highly citrulline specific. Conclusion Bronchiectasis is an unusual but potent model for the induction of autoimmunity in RA by bacterial infection in the lung. Our study suggests that the ACPA response is not citrulline specific during the early stages of tolerance breakdown but becomes more specific in patients with BR in whom BR/RA develops.